2020
DOI: 10.4274/jtgga.galenos.2019.2018.0138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mother-infant skin-to-skin contact immediately after birth on exclusive breastfeeding: a systematic review and meta-analysis

Abstract: In the new millennium, exclusive breastfeeding plays an important role in national and international policies. The effects of mother-infant skin-to-skin contact (SSC) after birth has been investigated in several studies. Given that there has been no overall estimate of this effects, the present study was conducted with the aim of investigating the effects of mother-infant SSC on the rate of exclusive breastfeeding through a systematic review and meta-analysis of randomized controlled trials. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 18 publications
3
36
0
8
Order By: Relevance
“…1 review-low [42] Mother-infant skin-to-skin contact to promote exclusive breastfeeding 1 review-critically low [43] Postnatal face-to-face contact with a health professional to promote breastfeeding duration and exclusivity 1 review-critically low [44] Breastfeeding mHealth/eHealth/telehealth Telephone support (mainly voice calls) during pregnancy and early post-partum for breastfeeding 1 review-high [45] 1 grey literature review Targeted client communication via mobile device (e.g., SMS, voice calls, apps with instant messaging) for breastfeeding 1 review-high [46] Internet support for breastfeeding 1 Some reviews are counted under more than one intervention type depending on the focus of the review.…”
Section: Characteristics and Quality Of Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 review-low [42] Mother-infant skin-to-skin contact to promote exclusive breastfeeding 1 review-critically low [43] Postnatal face-to-face contact with a health professional to promote breastfeeding duration and exclusivity 1 review-critically low [44] Breastfeeding mHealth/eHealth/telehealth Telephone support (mainly voice calls) during pregnancy and early post-partum for breastfeeding 1 review-high [45] 1 grey literature review Targeted client communication via mobile device (e.g., SMS, voice calls, apps with instant messaging) for breastfeeding 1 review-high [46] Internet support for breastfeeding 1 Some reviews are counted under more than one intervention type depending on the focus of the review.…”
Section: Characteristics and Quality Of Included Reviewsmentioning
confidence: 99%
“…The evidence regarding the benefit of antenatal breastfeeding education alone was insufficient [33]. Reviews supported the effectiveness of education and support in promoting exclusive breastfeeding [19,[35][36][37]43,44,70] as well as the benefits of peer and health professional counselling (including group approaches) in improving initiation, duration and exclusivity [35,36,[38][39][40][41].…”
Section: Breastfeeding Interventionsmentioning
confidence: 99%
“…Compared to separation at birth, SSC is effective in different areas of mother-child health, especially in improving indicators and prevalence of breastfeeding in infants under 6 months [ 27 , 28 ]. Specifically, it increases the percentage of infants on exclusive breastfeeding at 3 months and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it increases the percentage of infants on exclusive breastfeeding at 3 months and 6 months. Karimi et al [ 28 ] showed an effect of SSC started in the first 10 min of life compared to separation in improving the duration of exclusive breastfeeding for 3 months (odds ratio [OR] 2.47, 95% CI 1.73, 3.48) and for 6 months (OR 1.71, 95% CI 1.05, 2.78). Likewise, Moore et al [ 4 ] showed that SSC started immediately compared to separation increases the duration of breastfeeding by 3 months or more (RR 1.97, 95% CI 1.37, 2.83).…”
Section: Discussionmentioning
confidence: 99%
“…Sucking stimulus triggers oxytocin release, which gives rise to milk ejection. In addition, sucking is responsible for the strong emotional connection between mother and newborn through the skin-to-skin contact [27][28][29]. Prolonged breastfeeding may increase the duration of postpartum amenorrhea and promote circulation of oxytocin [30].…”
mentioning
confidence: 99%